Nitroalkene inhibition of pro-inflammatory macrophage effector function via modulation of signaling metabolite levels - Stevenson, Emily R.; O’Brien, James P.; Manuel, Allison M.; Uvalle, Crystal E.; Buchan, Gregory J.; Mullett, Steven J.; Lockwood, Karina; Suber, Tomeka; Freeman, Bruce A.; Gelhaus, Stacy L. (Frontiers in Physiology, 2025)
IntroductionClassically activated innate immune cells undergo a metabolic switch to aerobic glycolysis to support effector function. We report that the small-molecule nitroalkene 10-n-octadec-9-enoic acid (NO2-OA) attenuates the Warburg- like phenotype of aerobic glycolysis in lipopolysaccharide (LPS)-activated macrophages, thus inhibiting pro-inflammatory signaling.MethodsRAW264.7 and bone marrow derived macrophage were treated with LPS with and without NO2-OA or 1400W. Pro-inflammatory cytokines were measured by ELISA and protein expression was determined by immunoblot. Central carbon metabolites with and without 13C stable isotope tracing were measured using liquid chromatography-high resolution mass spectrometry.ResultsOverall, the present observations indicate that nitroalkene-induced changes in central carbon metabolism contribute to the anti-inflammatory actions of this class of multi-target lipid signaling mediators. Comparison of macrophage responses to NO2-OA with the inducible nitric oxide synthase (NOS2 and iNOS) inhibitor 1400W affirms that NO2-OA inhibition of NOS2 expression and activity alone was not sufficient to account for the decreases in pro-inflammatory cytokine expression. NO2-OA treatment reduced intracellular succinate levels, which may be attributed to a concomitant reduction in intracellular itaconate and reliance on glutamine, thereby contributing to hypoxia-inducible factor 1α (HIF1α) destabilization observed in LPS-activated macrophages.ConclusionThe current data provide additional perspective on the actions of this small-molecule electrophile, which is currently in a Phase 2 clinical trial for the treatment of obesity-related chronic pulmonary inflammation and associated airway dysfunction.